Role of Metalloproteinases in Diabetes-associated Mild Cognitive Impairment - Pereira, Vitoria Mattos; Pradhanang, Suyasha; Prather, Jonathan F.; Nair, Sreejayan (Current Neuropharmacology, 2025)
Diabetes has been linked to an increased risk of mild cognitive impairment (MCI), a condition characterized by a subtle cognitive decline that may precede the development of dementia. The underlying mechanisms connecting diabetes and MCI involve complex interactions between metabolic dysregulation, inflammation, and neurodegeneration. A critical mechanism implicated in diabetes and MCI is the activation of inflammatory pathways. Chronic low-grade inflammation, as observed in diabetes, can lead to the production of pro-inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), interleukin-1 beta (IL-1β), and interferon-gamma (IFNγ), each of which can exacerbate neuroinflammation and contribute to cognitive decline. A crucial enzyme involved in regulating inflammation is ADAM17, a disintegrin, and metalloproteinase, which can cleave and release TNF-α from its membrane-bound precursor and cause it to become activated. These processes, in turn, activate additional inflammation-related pathways, such as AKT, NF-κB, NLP3, MAPK, and JAK-STAT pathways. Recent research has provided novel insights into the role of ADAM17 in diabetes and neurodegenerative diseases. ADAM17 is upregulated in both diabetes and Alzheimer's disease, suggesting a shared mechanism and implicating inflammation as a possible contributor to much broader forms of pathology and pointing to a possible link between inflammation and the emergence of MCI. This review provides an overview of the different roles of ADAM17 in diabetes-associated mild cognitive impairment diseases. It identifies mechanistic connections through which ADAM17 and associated pathways may influence the emergence of mild cognitive impairment.
Keywords: T2DM